Identification of Germline Mutations in Melanoma Patients with Early Onset, Double Primary Tumors, or Family Cancer History by NGS Analysis of 217 Genes - Stolarova, Lenka (Biomedicines, 2020)
Cutaneous melanoma is the deadliest skin malignity with a rising prevalence worldwide. Patients carrying germline mutations in melanoma-susceptibility genes face an increased risk of melanoma and other cancers. To assess the spectrum of germline variants, we analyzed 264 Czech melanoma patients indicated for testing due to early melanoma (at <25 years) or the presence of multiple primary melanoma/melanoma and other cancer in their personal and/or family history. All patients were analyzed by panel next-generation sequencing targeting 217 genes in four groups: high-to-moderate melanoma risk genes, low melanoma risk genes, cancer syndrome genes, and other genes with an uncertain melanoma risk. Population frequencies were assessed in 1479 population-matched controls. Selected POT1 and CHEK2 variants were characterized by functional assays. Mutations in clinically relevant genes were significantly more frequent in melanoma patients than in controls (31/264; 11.7% vs. 58/1479; 3.9%; p = 2.0 × 10(−6)). A total of 9 patients (3.4%) carried mutations in high-to-moderate melanoma risk genes (CDKN2A, POT1, ACD) and 22 (8.3%) patients in other cancer syndrome genes (NBN, BRCA1/2, CHEK2, ATM, WRN, RB1). Mutations in high-to-moderate melanoma risk genes (OR = 52.2; 95%CI 6.6–413.1; p = 3.2 × 10(−7)) and in other cancer syndrome genes (OR = 2.3; 95%CI 1.4–3.8; p = 0.003) were significantly associated with melanoma risk. We found an increased potential to carry these mutations (OR = 2.9; 95%CI 1.2–6.8) in patients with double primary melanoma, melanoma and other primary cancer, but not in patients with early age at onset. The analysis revealed affected genes in Czech melanoma patients and identified individuals who may benefit from genetic testing and future surveillance management of mutation carriers.